Овладение учащимися навыками критического мышления и применение метода проектов на уроках информатики - Кабдуллина, А.Н. (My University, 2016)
The technology of development of critical thinking in the close connection with the use of project- based learning on computer science lessons is discussed in this article. Project activities are concentrated on the development of student’s creative abilities and critical thinking. The main purpose of the project-based learning is the formation of creative and critical thinking student.
Keywords: project-based learning; the technology of development of critical thinking; informatics